(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of Uzbekistan’s evolving role in the global community and international relations. It highlights key diplomatic initiatives undertaken by Uzbekistan, emphasizing its efforts to promote regional stability and foster cooperation among neighboring Central Asian states. The article also discusses Uzbekistan’s economic growth strategies, including trade partnerships and infrastructure projects aimed at enhancing connectivity. Furthermore, the article explores Uzbekistan’s cultural diplomacy and soft power initiatives, underscoring the country’s commitment to preserving and promoting its rich cultural heritage on the world stage. It also acknowledges Uzbekistan’s progress in improving human rights and its engagement in global peacekeeping efforts. Overall, the annotation summarizes the main themes covered in the article, providing valuable insights into Uzbekistan’s multifaceted approach to international relations and its aspirations for greater global influence.